Learning with others : collaboration as a pathway to college student success - Conrad, Clifton; Lundberg, Todd (Johns Hopkins University Press, 2022)
"How can colleges and universities engage students in ways that prepare them to solve problems in our rapidly changing world? Most American colleges and universities assimilate students into highly competitive undergraduate experiences. By placing achievement for personal and material gain as the bedrock of a college education, these institutions fail to educate students to become collaborative learners: people who are committed and prepared to join with others in developing promising solutions to problems that they share with others. Drawing on a three-year study of student persistence and learning at Minority-Serving Institutions, Clifton Conrad and Todd Lundberg argue that student success in college should be redefined by focusing on the importance of collaborative learning over individual achievement. Engaging students in shared, real-world problem-solving, Conrad and Lundberg assert, will encourage them to embrace interdependence and to value and draw on diverse perspectives. Learning with Others presents a set of core practices to empower students to enter, nourish, and sustain collaborative learning and outlines how to blend the roles and responsibilities of faculty, staff, and students; how to adopt best practices for receiving and giving feedback on problem-solving; and how to anchor a curriculum in shared problem-solving. Bringing together lessons learned from more than 300 interviews, along with notes from 14 campus visits, 3 national convenings, and examples from across our nation's colleges and universities, Conrad and Lundberg explore ways in which successful antiracist networks of problem-solvers are learning to contribute to the flourishing of their communities on campus and far beyond. Outlining strategies for identifying and dismantling barriers to participation, Learning with Others will pique interest among faculty, students, and administrators in higher education and a wide range of external stakeholders--from families and communities to policymakers and funders." --